The effects of cross crawl and owl exercises on memory and focus in early childhood - Irmayanti, Ni Luh; Suma, Ketut; Ketut Desia Tristiantari, Ni (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Cognitive abilities such as memory and concentration are essential for early childhood development, influencing academic readiness and social adjustment. However, many children face challenges in sustaining attention and retaining information, and existing intervention methods often lack integration and movement-based engagement. This study aims to evaluate the effectiveness of a combined Brain Gym intervention—Cross Crawl and The Owl exercises on improving memory and concentration in early childhood. A quasi-experimental design with pre-test and post-test control groups was employed, involving 60 children aged 4–6 years from Skoebi-Do Child Care Centre, Bali. Participants were randomly assigned to an experimental group (receiving both Cross Crawl and The Owl techniques) and a control group (receiving only Cross Crawl). Data were collected using structured observation instruments, which had been validated and tested for reliability to ensure accurate measurement of cognitive outcomes. The findings demonstrated significant improvements in memory and concentration among children in the experimental group compared to the control group. These results indicate that integrative Brain Gym interventions are more effective in stimulating core cognitive functions during early childhood. This study contributes to the growing evidence supporting movement-based educational strategies as a practical and accessible approach for enhancing cognitive development in early learners.